FINANCIAL LEASING - Mavila H., Daniel (2003)
This essay deals with the several financial resources an enterprise counts on to purchase assets of the kind real state or chattels. A resource that does not risk solvency is the lease, through the retro-leasing variant that allows to obtain working capital by selling one of its fixed assets without giving its use up.